Changes in breeding soundness evaluation during a breeding season - A.W. Thompson; T.T. Marston; M. Sanderson; P. Chenoweth (Kansas Agricultural Experiment Station Research Reports, 2004)
Breeding-soundness evaluations are a common tool in the beef industry to test a bull's potential fertility. These evaluations place a bull into one of three categories: satisfactory, unsatisfactory, or deferred. These categories only refer to the bull at a specific time, and his status can and will change over time. The purpose of this report is to explain and demonstrate the changes in a bull's breeding- soundness evaluations during a breeding season.
Keywords: Cattlemen' s Day; 2004; Kansas Agricultural Experiment Station contribution; no. 04-242-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 923; Beef; Breeding; Soundness